In silico study of the bioactive compounds in Peronema canescens Jack (Sungkai) leaf infusion targeting VEGFR-2: Insights into anticancer potential - rahayu, Ika; Sudrajat, Susana Elya; Timotius, Kris Herawan (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Peronema canescens Jack, commonly known as sungkai, is a medicinal plant traditionally consumed as a herbal infusion. It has demonstrated potential anticancer properties attributed to its bioactive constituents, particularly clerodane-type diterpenoids known as peronemins. The anticancer potential of these compounds can be preliminarily explored using in silico approaches. Of particular interest are the reported the cytotoxic effects of sungkai leaves against cancer cell lines and their interactions with angiogenesis-related targets, including vascular endothelial growth factor receptor-2 (VEGFR-2). VEGFR-2 is a critical tyrosine kinase receptor that regulates angiogenesisa and Its aberrant activation contributes to tumor growth and metastasis. Consequently, VEGFR-2 represents a well-established target for anticancer therapy development. Objectives: This study aims to investigate the bioactive compounds present in sungkai leaf infusion using liquid chromatography-mass spectrometry (LC-MS), and to predict their interactions with VEGFR-2 through in silico molecular docking analysis. Methods: Phytochemical profiling of the leaf infusion was conducted using LC-MS. Molecular docking was performed using PyRx 0.8 integrated with AutoDock Vina to assess ligand-protein interactions between selected compounds and VEGFR-2 (PDB ID: 2QU5). The resulting interactions were visualized using Discovery Studio.Results: LC-MS analysis identified ten major compounds in the leaf infusion, consisting of one alkaloid (gentiatibetine) and nine flavonoids. Molecular docking analysis revealed that genkwanin and acacetin-7-galactoside exhibited strong binding affinities toward VEGFR-2 (−9.6 and −9.2 kcal/mol, respectively), approaching that of the referencesorafenib (−11.2 kcal/mol). Both compounds interacted with key catalytic residues, suggesting their potential to inhibit VEGFR-2 by stabilizing its inactive conformation.Conclusion: This study provides the first to report that sungkai leaf infusion is rich in flavonoid compounds two of which exhibit strong anti-VEGFR-2 activity. These findings suggest the potential of sungkai leaf infusion as a natural anticancer agent and support the needfor further in vitro and in vivo validation.